2021
DOI: 10.3390/antiox10081301
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Water Deficit Irrigation on Phenolic Composition and Antioxidant Activity of Monastrell Grapes under Semiarid Conditions

Abstract: The high phenolic compound content of grapes makes them an important source of natural antioxidants, among other beneficial health properties. Vineyard irrigation might affect berry composition and quality. Regulated deficit irrigation (RDI) is a widely used strategy to reduce the possible negative impact of irrigation on grapes, improving grape composition and resulting in water savings. Monastrell grapevines (Vitis vinifera L.) grown in eastern Spain were subjected to two water regime strategies: rainfed (no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 63 publications
0
21
1
Order By: Relevance
“…In this regard, under rainfed conditions, MC80 showed the highest TCP skin–seed content and MS49 the highest anthocyanin content, exceeding those of MC72 (which had the lowest contents) by 61% and 79%, respectively. Although phenolic quality is associated with a reduction in production and a smaller berry size [ 27 , 61 ], the present results also show a strong genotypic component since the differences in phenolic variables did not always coincide with differences in the yield variables. For example, the lowest production and the smallest berry size of MC72 and MC19 ( Table 2 ) did not correlate with the highest TCP skin–seed content ( Table 4 ), as might be expected, while the highest production of MS104 did correlate with one of the lowest TCP skin–seed contents.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…In this regard, under rainfed conditions, MC80 showed the highest TCP skin–seed content and MS49 the highest anthocyanin content, exceeding those of MC72 (which had the lowest contents) by 61% and 79%, respectively. Although phenolic quality is associated with a reduction in production and a smaller berry size [ 27 , 61 ], the present results also show a strong genotypic component since the differences in phenolic variables did not always coincide with differences in the yield variables. For example, the lowest production and the smallest berry size of MC72 and MC19 ( Table 2 ) did not correlate with the highest TCP skin–seed content ( Table 4 ), as might be expected, while the highest production of MS104 did correlate with one of the lowest TCP skin–seed contents.…”
Section: Discussioncontrasting
confidence: 53%
“…Preventive and adaptive measures need to be taken by the wine sector if the adverse effects of climate change are to be mitigated [ 18 , 19 , 20 , 21 ]. A short-term preventive measure could be the use of deficit irrigation techniques, which may improve the quality of grapes and wine [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ] while maintaining good yields—as long as the water-stress threshold is not exceeded (which would lead to a reduction in wine quality) [ 30 ]. However, Fraga et al (2018) [ 31 ] observed that, in hot and dry regions in Portugal, yields were significantly reduced even when efficient irrigation was available, a consequence of water and heat stress; daytime temperatures above 35 °C negatively affect flowering and fruit set [ 32 ] and therefore yield.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a deeper understanding of the correlation between these polyphenolic compounds and their free radical scavenging abilities is needed. Pearson’s correlation analysis indicated a positive correlation between total phenolic acids, flavonoids, DPPH, and ABTS (indicating free radical scavenging ability) [ 22 , 49 , 50 ]. There were also multiple groups of significant or extremely significant positive correlations between ABTS, HSRA, FRAP, and DPPH, and the components of polyphenols in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Fruit polyphenol composition and nutritional quality are affected and regulated by many factors, including variety, maturity, cultivation management, and environmental stress [ 22 ]. The improper use of the water-deficit approach can seriously affect the processes of various physiological and biochemical reactions in plants, such as relative leaf water content, photosynthetic fluorescence parameters, stomatal response, osmotic regulation, reactive oxygen species, and antioxidant response [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Different irrigation regulation strategies have also been applied in agricultural production, such as regulated deficit irrigation (RDI; Pérez-Álvarez et al, 2021), partial root-zone drying (PRD; Santos et al, 2021) and alternate partial root-zone irrigation (APRI; Kang and Zhang, 2004). Studies on eggplants in greenhouse found that APRI increased the fruit yield and WUE (Du et al, 2005).…”
Section: Introductionmentioning
confidence: 99%